La sobreprotección y el factor de riesgo en el desarrollo psicosocial de los niños. - Naranjo Robayo, Erika Alexandra (2021)
The objective of this research is to analyzing the relationship between the children characteristics overprotection and the development psychosocial stages for parents to know, for breeding their children. Since overprotection directly affects the cognitive and emotional development of the child and most parents have not given importance to this and psychosocial development , so it is a constant process of transformations that takes place according with the environment interaction that the child has, the research provided important information about the two used variables, methodologically a mixed approach , the population was made up of 14,600 published documents , between 2004 and 2020, the sample represents 32 documents, with a type of bibliographic research, cross-sectional design, descriptive and exploratory research level, limited in the last 16 years and the databases of Dialnet, Redalyc , Google Academic, Scielo and regarding the techniques Spanish articles to establish a criteria search were carried out in this research. Cataloged by country, journal of publication, and place of search according to the year of publication, title and type of document for data collection such as: accumulate and select references, writings, final corrections and revisions were also used. Finally, after conducting the research and inquiring into various scientific sources, as a conclusion, parents fear seeing their children grow, and they do not allow their proper development and this has serious consequences in the future.